Impact of vaping restrictions in public places on smoking and vaping in the United States—evidence using a difference‐in‐differences approach. (19th September 2022) - Cheng, Kai‐Wen; Liu, Feng; Pesko, Michael F.; Levy, David T.; Fong, Geoffrey T.; Cummings, K. Michael
Abstract: Aims: To estimate whether and to what extent extending indoor smoking restrictions to include electronic cigarettes (ECs) impact the use of ECs and cigarette smoking among adults in the United States. Design: Observational study using a linear probability model and applying a difference‐in‐differences analysis. Setting: United States. Participants: People aged 18–54 who lived in US counties where comprehensive indoor smoking laws in bars, restaurants and private work‐places have been in place prior to 2010 ( n  = 45 111 for EC use analysis, n  = 75 959 for cigarette use analysis). Measurements: Data on cigarette smoking, use of ECs and place of residence from the Tobacco Use Supplement of the Current Population Survey (TUS‐CPS 2010–11, 2014–15 and 2018–19) were combined with the American Nonsmokers' Rights Foundation (ANRF) database of state and local indoor smoking and vaping restriction laws. Findings: Indoor vaping restriction (IVR) coverage was not significantly associated with the likelihood of adult EC use [coefficient estimate = 0.001; 95% confidence interval (CI) = −0.009, 0.013, P ‐value = 0.783]. In addition, IVR coverage was not significantly associated with adult cigarette smoking (coefficient estimate = −0.00; 95% CI = −0.016, 0.015, P ‐value = 0.954). The non‐significant results appeared in different socio‐demographic subgroups. Conclusions: IVRs do not appear to decrease electronic cigarette use among US adults. There is no evidence that IVRs increase or decrease cigarette smoking among US adults.